α-Glucosidase Inhibitory Effect and Simultaneous Quantification of Three Major Flavonoid Glycosides in Microctis folium - Wen-Cai Ye; Ying Wang; Xian-Tao Zhang; Xiao-Qi Zhang; Ru Yan; Peng Li; Ping Li; Yan-Gan Chen; Qing-Wen Zhang (Molecules, 2013)
Microctis Folium, the leaves of Microcos paniculata L., is a commonly used herbal tea material. The methanol extract of Microctis Folium and its principle compounds vitexin (1), isovitexin (2) and isorhamnetin 3-O-β-D-rutinoside (3) were investigated for their α-glucosidase inhibitory effects. The extract showed strong α-glucosidase inhibitory effect (IC50 = 61.30 μg/mL) and the three flavonoid glycosides 1–3 exerted satisfactory α-glucosidase inhibitory effects, with IC50 values of 244.0 μM, 266.2 μM and 275.4 μM, respectively. A simple and reliable HPLC-DAD method was developed for the quantification of the three flavonoid glycosides in Microctis Folium and applied successfully to determine contents of these components in samples collected from different locations. This study suggested that Microctis Folium may be a promising candidate for development of herbal antidiabetes drugs, and vitexin, isovitexin and isorhamnetin 3-O-β-D-rutinoside can be the biomarkers and chemical markers for this plant substance.